“Análisis del efecto por deficiencia del hierro en la ganancia de peso en lechones”. - Nazareno Heredia, Yulliza Leonela (2022)
This thesis deals with the analysis of the effect of iron deficiency on weight gain in piglets. Highlighting the problem of anemic pigs that represent an obvious loss for farmers. Piglets are at risk of developing iron deficiency anemia because they are born with levels that last only a few days. The main objective of this project has been to determine the effect of iron deficiency on weight gain in piglets. This disorder affects piglets of all breeds, but its results are especially serious in animals of high-performance breeds. The occurrence of iron deficiency in suckling piglets has been known for a long time. There are numerous ways in which piglets can be given iron supplements, either (1) orally (by mouth) or (2) parenterally (by injection) to meet their iron needs. Much of the oral iron is not absorbed and is excreted in the feces. Studies are shown showing that low hemoglobin levels during weaning significantly inhibit growth, and even when hemoglobin levels are restored. A finding is shown that demonstrates that there is a high probability that pigs will develop anemia and iron deficiency after weaning. Being the weight of pigs with anemia of 0.82 kg with less than 3 weeks after weaning, unlike normal Hb piglets at weaning (P < 05). The physiological aspects of the piglet are often influenced by its environment. Providing the correct nutrients will lead to optimal weight gain. Prevention is a pertinent recommendation, which is carried out in the same way and with the same drugs that are used to treat anemic piglets